Effects of a short interpregnancy interval on pregnancy outcomes - Kisuule, Castro (Department of Obstetrics and Gynaecology, 2018)
The interval between one pregnancy and the next may affect the outcome of pregnancy. Both short and long interpregnancy intervals (IPI) have been associated with adverse pregnancy outcomes and most of these occur with a short IPI. Our primary objective was to determine the effects of a short IPI (< 24 months) compared with a long IPI (≥ 24 months) on the subsequent potentially viable pregnancy in women who received antenatal care (ANC) in the secondary level hospitals in the Metro-West area of Cape Town. The secondary objective was to review possible determinants of a short IPI. Methods: This was a pilot descriptive cross-sectional study conducted between 1st September 2016 and 28th November 2016. One hundred and thirty women who were Para 2 were recruited to the study in the early postnatal period. Sixty women were recruited into the short IPI group (<24 months) and 70 to the long IPI group (≥24months). Questionnaire-based interviews were conducted and data were entered using Microsoft Excel 2012 spread sheets. Statistical analysis was done using Stata® Edition 13. Results: We analysed the data for both short and long IPI and found that there were no significant differences in preterm birth, abruptio placentae, preterm prelabour rupture of membranes (PPROM) and low birth weight. There was however a significant difference in the number of small-for-gestational- age (SGA) babies. In the short IPI group, 19 women (31.7%) had SGA babies in comparison to the long IPI group where 7 women (10%) had SGA babies( p = 0.015). Of the 130 respondents, 79 women (60.8%) had unintended pregnancies, 44 (73%) with a short IPI vs 35 (50%) with a long IPI (p = 0.017). Women with a long IPI were more likely to have a different partner for the subsequent pregnancy (p= 0.002). Women in relationships longer than 5 years were more likely to have a long IPI (p = 0.049). Thirty-eight women (63.3%) with a short IPI would have preferred the pregnancy later compared to 11 women (15.7%) with a long IPI (p<0.001). There were 27 (38%) women who supported themselves financially in the long IPI group compared with 8 (13%) with a short IPI (p=0.001). A long IPI was associated with more formal employment and professional careers compared to a short IPI (p= 0.002). In the long IPI group 10 women (7%) had professional positions compared with none in the short IPI group (p=0.002). There were no significant differences in breastfeeding duration, contraception use and knowledge, social habits, previous obstetric history, educational status or emotional support between the two groups. Conclusion: In our study, of all the pregnancy outcomes investigated, small-for-gestational age was the only clinical outcome significantly associated with a short IPI. There were differences in pregnancy intendedness, duration of relationships, financial support and employment between the two groups. The majority of women with a short IPI (63.3%) would have preferred the index pregnancy to have occurred later.